Accumulation of specific RNAs encoding transcriptional factors and stress response proteins against a background of severe depletion of cellular RNAs in cells infected with herpes simplex virus 1 - Khodarev, Nikolai N. (The National Academy of Sciences, 1999)
Herpes simplex virus 1 encodes several functions to preclude the shutoff of host response to infection, including degradation of mRNA immediately after infection. To determine whether any cellular mRNAs accumulate in infected cells against a background of severe loss of host RNA, we hybridized cDNAs derived from three different cell lines infected with wild type and a mutant virus to a DNA array containing probes for 588 human genes representing different functional groups. The results were that (i) infected cells accumulated at levels above those of mock-infected cells, a small number of transcripts representing transcriptional factors that could regulate gene expression both positively and negatively, and one stress response protein (GADD45), (ii) the amount and nature of the accumulated transcripts showed limited variability depending on the cell and virus, and (iii) at least some of the proteins encoded by the accumulated transcripts could benefit either the virus or the host.